The Agency of the disabled- female identity at war time in the Lebanese Hanan ALshayhk The Story Of Zahraby and the Afghani Khaled Alhusinie A Thousand Splendid Suns by. A Comparative Study. - محمود , عيد حسن; حسن , طلال محمّد; عبد الرحمن, محمّد سليم (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The research basically examines the assumption claimed that the disabled –female identities counter the discourse of the fabricated and declined feminine force physical disability texts .Hence, it raises the following questions: are these identities are trying to empower the inner-self imploring created or countered resistance to gradually incorporated to war time ?Is eliminating the flaw of the fabricated disability come into possession the feminine- political struggling role ,which embodies the disabled female rebellious claimed to a legal right? In conclusion, the agency of the disabled-female identity is dynamically a performance concept and condescending agency start from the secret negotiation phase ,empowering and participating the female self to breach the physical imaginative narrative. Then, the public breaching phase, in which the female -self breaks the chain. Finally ,the inherent liminality phase at which the female disability to be fixed, though she tries to release the society grasp and the social norms which has been stuck in-between two binaries: the female femininity not recognizing her existence and the social psychosis claimed her body unhealthy and categorized her status unhealthier.